These impossible things : [a novel] - El-Wardany, Salma (Grand Central Publishing, 2022)
"It's always been Malak, Kees, and Jenna against the world. Since childhood, under the watchful eyes of their parents, aunties and uncles, they've learned to live their own lives alongside the expectations of being good Muslim women...With growing older and the stakes of love and life growing higher, the delicate balancing act between rebellion and religion is becoming increasingly difficult to navigate. As their lives begin to take different paths, Malak, Kees, and Jenna--now on the precipice of true adulthood--must find a way back to each other as they reconcile faith, family, and tradition with their own needs and desires"--